2021
DOI: 10.3390/jcm10143093
|View full text |Cite
|
Sign up to set email alerts
|

Central and Branch Retinal Artery Occlusion—Do They Harbor the Same Risk of Further Ischemic Events?

Abstract: Purpose: Retinal artery occlusion (RAO) is associated with an increased risk of cardiovascular events such as ischemic stroke and myocardial infarction, but whether different RAO subtypes such as central retinal artery occlusion (CRAO) or branch retinal artery occlusion (BRAO) carry similar risk of these events is unclear. Our aim was to determine whether the risk of cardiovascular events differs between CRAO and BRAO. Methods: This single-center, retrospective study included 131 patients hospitalized in our c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 43 publications
0
23
2
Order By: Relevance
“…The vast majority of RAO affects elderly patients, in which traditional cardiovascular risk factors have important underlying role in the onset of the disease. The presence of numerous cardiovascular risk factors in patients with RAO has been reported by multiple studies [1][2][3][4][5][6][7][8]10,13,15,18,20,21,24,25]. In a study by Callizo et al, 78% of patients had at least one undiagnosed cardiovascular risk factor at the time of CRAO [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The vast majority of RAO affects elderly patients, in which traditional cardiovascular risk factors have important underlying role in the onset of the disease. The presence of numerous cardiovascular risk factors in patients with RAO has been reported by multiple studies [1][2][3][4][5][6][7][8]10,13,15,18,20,21,24,25]. In a study by Callizo et al, 78% of patients had at least one undiagnosed cardiovascular risk factor at the time of CRAO [3].…”
Section: Discussionmentioning
confidence: 99%
“…All inpatients treated for RAO (ICD-10: H34.1, H34.9) at the Department of Ophthalmology between 2009 and 2020 were included in this retrospective study. The inclusion of patients with RAO in the study was described previously [ 21 ]. The control group included sex- and age-matched patients without ocular vascular occlusive disorders who were randomly selected from a total of 15,373 patients undergoing cataract surgery between 2009 and 2020 at the Department of Ophthalmology.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,[6][7][8] However, it is unclear whether there is a difference in comorbidities, including cardiovascular diseases, according to RAO subtype, and whether there is a difference in mortality compared with that in the general population. [9][10][11][12] Furthermore, there are few reports on CRAO incidence in large population groups 3,[13][14][15] ; in particular, data on noncentral RAO is scarce, with only one report on annual incidence. 5 Additionally, there are conflicting reports regarding whether CRAO or noncentral RAO is more prevalent.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies found that, at least, a new cardiovascular risk factor was found in approximately 80% of patients with CRAO, and carotid stenosis or cardioembolism were observed in approximately 40% of CRAOs [ 42 , 50 ]. Patients with BRAO have a risk of stroke, myocardial infarction, and all-cause mortality comparable to CRAO [ 51 ]. Recent studies investigating the risk factors in CRAO are summarized in Table 1 .…”
Section: Retinal Artery Occlusionmentioning
confidence: 99%